2017
DOI: 10.1111/mmi.13760
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl reduction by YmfI in Bacillus subtilis prevents accumulation of an inhibitory EF‐P modification state

Abstract: Translation elongation factor P (EF-P) in Bacillus subtilis is required for a form of surface migration called swarming motility. Furthermore, B. subtilis EF-P is post-translationally modified with a 5-aminopentanol group but the pathway necessary for the synthesis and ligation of the modification is unknown. Here we determine that the protein YmfI catalyzes the reduction of EF-P-5 aminopentanone to EF-P-5 aminopentanol. In the absence of YmfI, accumulation of 5-aminopentanonylated EF-P is inhibitory to swarmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 39 publications
(65 reference statements)
1
27
0
Order By: Relevance
“…Further, we showed that 5-aminopentanone, but not unmodified EF-P, is inhibitory to swarming motility, as abolishing posttranslational modification of EF-P altogether by mutation of Lys32 to an arginine suppressed the ymfI swarming defect ( 24 ). Here, we take advantage of EF-P activity in the absence of modification to identify other enzymes that act upstream of YmfI in the EF-P modification pathway ( 24 ). Mass spectrometry analyses of EF-P purified from wild-type (WT) B. subtilis and each of the modification mutants revealed that EF-P can retain incomplete modifications.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Further, we showed that 5-aminopentanone, but not unmodified EF-P, is inhibitory to swarming motility, as abolishing posttranslational modification of EF-P altogether by mutation of Lys32 to an arginine suppressed the ymfI swarming defect ( 24 ). Here, we take advantage of EF-P activity in the absence of modification to identify other enzymes that act upstream of YmfI in the EF-P modification pathway ( 24 ). Mass spectrometry analyses of EF-P purified from wild-type (WT) B. subtilis and each of the modification mutants revealed that EF-P can retain incomplete modifications.…”
Section: Introductionmentioning
confidence: 96%
“…We have recently shown that YmfI reduces 5-aminopentanone to 5-aminopentanol in the final step of EF-P modification ( 24 ). Further, we showed that 5-aminopentanone, but not unmodified EF-P, is inhibitory to swarming motility, as abolishing posttranslational modification of EF-P altogether by mutation of Lys32 to an arginine suppressed the ymfI swarming defect ( 24 ). Here, we take advantage of EF-P activity in the absence of modification to identify other enzymes that act upstream of YmfI in the EF-P modification pathway ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The function of both EF-P and e/aIF-5A in assisting polyproline translation depends on posttranslational modification (8,14). In this regard, EF-P can be ␤-lysylated (15)(16)(17), 5-aminopentolylated (18)(19)(20), and rhamnosylated (7,21,22). The eukaryotic/archaeal ortholog e/aIF5A, in contrast, strictly depends on (deoxy)hypusination (23).…”
mentioning
confidence: 99%
“…The peptidase U32 protein YrrN is one member of the yrrMNO operon which is important for the biosynthesis of 5-hydroxyuridine, YrrN is involved in the synthesis of 5methoxyuridine (Nguyen et al 2011). The cytoplasmic ClpP-like germination protease TepA is involved in spore outgrowth in B. subtilis, and is not proposed to be a signal peptide peptidase but to degrade a specialized family of small DNA-binding proteins during the process of spore outgrowth (Traag et al 2013;Westers et al 2004a).YmfH is identi ed by the presence of Peptidase_M16 and Peptidase_M16_C domains, and is predicted to encode uncharacterized zinc protease with unknown speci city (Hummels et al 2017).In this study, the deletion of any of the four proteases improved the secretion of AiiO-AIO6, but the degree of improvement was different. Their effect on the secretion of AiiO-AIO6 in B. subtilis was YwpE > YrrN > TepA or YmfH, which may be due to the difference in the degradation ability of these proteases to AiiO-AIO6 or the degradation ability of the proteins assisting the secretion of AiiO-AIO6.…”
Section: Discussionmentioning
confidence: 99%